2006
DOI: 10.1242/dev.02383
|View full text |Cite
|
Sign up to set email alerts
|

Müllerian inhibiting substance regulates its receptor/SMAD signaling and causes mesenchymal transition of the coelomic epithelial cells early in Müllerian duct regression

Abstract: Examination of Müllerian inhibiting substance (MIS) signaling in the rat in vivo and in vitro revealed novel developmental stageand tissue-specific events that contributed to a window of MIS responsiveness in Müllerian duct regression. The MIS type II receptor (MISRII)-expressing cells are initially present in the coelomic epithelium of both male and female urogenital ridges, and then migrate into the mesenchyme surrounding the male Müllerian duct under the influence of MIS. Expression of the genes encoding MI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
76
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(79 citation statements)
references
References 60 publications
3
76
0
Order By: Relevance
“…2 A-C), which lends support to the dual epithelial/mesenchymal potential ascribed to the ovarian coelomic epithelium (34,35). Interestingly, whereas ovarian cancer cells express the surface marker EpCam (36,37), the CE LRCs were negative (see Fig.…”
Section: H2b-gfp 3 Month Chasementioning
confidence: 58%
“…2 A-C), which lends support to the dual epithelial/mesenchymal potential ascribed to the ovarian coelomic epithelium (34,35). Interestingly, whereas ovarian cancer cells express the surface marker EpCam (36,37), the CE LRCs were negative (see Fig.…”
Section: H2b-gfp 3 Month Chasementioning
confidence: 58%
“…CTNNB1 seemed a particularly interesting candidate gene, since β-catenin is a downstream effector of both AMH and WNT signaling pathways, which may function cooperatively in mediating Müllerian duct regression [24]. Whether the effect of AMH involves WNT signaling in the Müllerian mesenchyme is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…The present studies were undertaken to determine the agents with which MIS could be used most efficaciously. For example, MIS exerts its effect in the embryonic urogenital ridge by activating MISRII, Alk2 and Alk3, and the Smad 1͞5͞8 differentiation and growth inhibitory pathway (35). In addition, MIS up-regulates pocket proteins p130 and p107 in human ovarian (10) and endometrial cancer cell lines (9).…”
Section: Discussionmentioning
confidence: 99%
“…Comprehensive studies in our laboratory, and in those of many others, have shown that MIS downstream signal transduction pathways include MISRII (28)(29)(30), the type I receptors Alk2 (31) and Alk3 (32), Smads 1͞5͞8 (33)(34)(35), cyclin-dependent kinase inhibitors (4, 9, 10), and cytokine-inducible pathways (36)(37)(38)(39), suggesting mechanisms of action that are potentially different from those of most cytotoxic drugs.…”
Section: Ullerian Inhibiting Substance (Mis) May Have Its Most Im-mentioning
confidence: 93%